A ruthenium single atom nanozyme-based antibiotic for the treatment of otitis media caused by Staphylococcus aureus - Wang, Jie; Gong, Rui; Yang, Ming; Wu, Xi; Li, Ziwei; Huang, Haibing; Yan, Xiyun; Wang, Daji (Frontiers in Chemistry, 2024)
Staphylococcus aureus (S. aureus) infection is a primary cause of otitis media (OM), the most common disease for which children are prescribed antibiotics. However, the abuse of antibiotics has led to a global increase in antimicrobial resistance (AMR). Nanozymes, as promising alternatives to traditional antibiotics, are being extensively utilized to combat AMR. Here, we synthesize a series of single-atom nanozymes (metal-C3N4 SANzymes) by loading four metals (Ag, Fe, Cu, Ru) with antibacterial properties onto a crystalline g-C3N4. These metal-C3N4 display a rob-like morphology and well-dispersed metal atoms. Among them, Ru-C3N4 demonstrates the optimal peroxidase-like activity (285.3 U mg–1), comparable to that of horseradish peroxidase (267.7 U mg–1). In vitro antibacterial assays reveal that Ru-C3N4 significantly inhibits S. aureus growth compared with other metal-C3N4 even at a low concentration (0.06 mg mL–1). Notably, Ru-C3N4 acts as a narrow-spectrum nanoantibiotic with relative specificity against Gram-positive bacteria. Biofilms formed by S. aureus are easily degraded by Ru-C3N4 due to its high peroxidase-like activity. In vivo, Ru-C3N4 effectively eliminates S. aureus and relieves ear inflammation in OM mouse models. However, untreated OM mice eventually develop hearing impairment. Due to its low metal load, Ru-C3N4 does not exhibit significant toxicity to blood, liver, or kidney. In conclusion, this study presents a novel SANzyme-based antibiotic that can effectively eliminate S. aureus and treat S. aureus-induced OM.